Pengaruh Panjang Elektrode Sangkar Delta pada Nilai Resistans Pentanahan di Lokasi Sempit - Harnoko Stephanus (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2016)
Grounding rod is more practical than grounding plate or grounding strip. Grounding resistance value must be set as small as possible. But, it is hard to approach the standard grounding resistance value. There are some methods used to reduce grounding resistance like paralleling ground rod, extending ground rod, or enlarging ground rod diameter. This paper explains the effect of length variation of delta cage electrode (dimension of delta side is 1 meter) on single ground rod resistance value. In this paper, ground rod’s length and diameter are 1.5 meters and 10 millimeters respectively. Ground rod is planted on the ground while the but is on land surface. Grounding resistance value of that single ground rod then is being compared with grounding resistance value of the combination of single ground rod and the delta cage electrode (dimension of delta side is 1 meter). After this research, we can conclude that: (a) delta cage electrode (its side 1 m) with three edge rod (length 0.5 meters, 1 meter and 1.5 meters; diameter 10 millimeters) can minimize grounding resistance value of single ground rod (length 1.5 meters, diameter 10 millimeters) by 33 ohm, 45 ohm, dan 50 ohm; (b) delta cage electrode (its side 1 m) with six edge rod (length 0.5 meters, 1 meter, and 1.5 meters; diameter 10 millimeters) can minimize grounding resistance value of single ground rod (length 1.5 meters, diameter 10 millimeters) by 45 ohms, 52 ohms dan 56 ohms.